Strategic Analysis Of Business Mode Canvas At Es Teh Indonesia Kebun Pramuka Banjarmasin - Izzati, Ridha Nur; Wulandari, Dyah Sri; Analisa, Analisa (Doctoral Program of Social Science Pasundan University, 2025)
The Business Model Canvas is a business model of a logical description of how an organization creates, delivers and captures value. There are nine basic building blocks of the business model canvas that show how to think about how the company is more productive. The nine blocks are customer segments, value propositions, channels, customer relationships, revenue streams, key resources, key activities, key partnerships, and cost structures. After that, it is divided into two sides, the left side as logic and the right side as creativity. Objective: This study aims to analyze the Business Model Canvas strategy and swot analysis, to be used in the promotion of coffee